Branding European cities in the context of tourism development: current trends and challenges (using the example of London, Paris and Amsterdam) - Savchenko, Anastasiia; Kostrikov, Sergiy (Human Geography Journal, 2025)
This study explores the interconnected concepts of branding and identity, emphasizing their substantial influence on the tourist image of cities. To examine the practical application of branding strategies, the research focuses on European cities, a region that has solidified its position in the global tourism market, recording 747 million international arrivals in 2024. Accordingly, the objective of this study is to identify current trends in tourism branding within European cities through the application of GIS technologies, while also critically assessing the challenges and limitations faced by key urban destinations, specifically London, Paris, and Amsterdam. The findings indicate that London (ranked 1st ), Paris (3rd), and Amsterdam (10th) hold prominent positions in the Brand Finance Global City Index 2024, which evaluates cities based on their ability to attract investment, talent, and visitors. These rankings underscore the strategic role of branding in shaping global perceptions, fostering economic growth, and enhancing urban competitiveness on an international scale. By offering distinct branding approaches, these cities continue to reinforce their unique identities within the tourism sector. This study examines the distinctive branding characteristics of three major European cities: London, Paris, and Amsterdam, each of which has cultivated a unique urban identity that contributes to its global reputation. London is recognized for its royal heritage, juxtaposing historical landmarks with modern architectural developments. The city is also a global fashion hub, hosting the prestigious London Fashion Week and offering renowned shopping districts. Paris, widely regarded as the capital of love, fashion, and culture, is intrinsically linked to romantic literary figures and celebrated poets. Like London, Paris is home to Fashion Week, along with a vast array of luxury boutiques that reinforce its status as an epicenter of elegance. Amsterdam, characterized by its bicycle-friendly infrastructure, iconic tulip fields, and picturesque canals, represents a notable example of urban rebranding, adapting its identity to modern tourism trends. The study employs GIS-based analysis in QGIS, alongside statistical and informational resources, to explore the branding dimensions and tourism dynamics of these cities. A key challenge identified across all three locations is overtourism, which generates a range of socio-economic and infrastructural concerns. In London, overtourism exacerbates the housing crisis, prompting local authorities to develop new residential complexes within the Grey Belt. In Paris, the prevalence of pickpocketing, particularly around tourist landmarks such as the Eiffel Tower, has raised security concerns, necessitating enhanced police patrols and surveillance infrastructure. Amsterdam, meanwhile, faces challenges linked to its tolerant drug policies, which have fueled drug tourism. While local regulations exist to manage recreational drug use, stricter policies may be required to mitigate the negative effects associated with this phenomenon. This paper underscores the complexities of urban branding and tourism management, demonstrating how cities must continuously adapt to evolving visitor expectations, economic shifts, and policy challenges to maintain their global appeal. The relevance of this study stems from the increasing significance of city branding as a strategic tool in the global competition for tourist flows and international visibility. As cities seek to enhance their appeal and differentiate themselves in the highly competitive tourism sector, understanding the branding characteristics and challenges faced by leading European urban destinations becomes essential. Our research provides valuable insights into the evolving dynamics of tourism branding, offering an in-depth analysis of the branding strategies employed by London, Paris, and Amsterdam, as well as the socio-economic issues that accompany their global prominence.